2011
DOI: 10.1101/gad.16746011
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of Escherichia coli Hfq hexamers in DsrA binding

Abstract: Hfq is a bacterial post-transcriptional regulator. It facilitates base-pairing between sRNA and target mRNA. Hfq mediates DsrA-dependent translational activation of rpoS mRNA at low temperatures. rpoS encodes the stationary-phase s factor s S , which is the central regulator in general stress response. However, structural information on Hfq-DsrA interaction is not yet available. Although Hfq is reported to hydrolyze ATP, the ATP-binding site is still unknown. Here, we report a ternary crystal complex structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
95
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(108 citation statements)
references
References 45 publications
(79 reference statements)
10
95
0
3
Order By: Relevance
“…If this were the case, it would be possible that the proximal side of Hfq binds the terminator poly(U) tail, while the internal stem-loop/U-rich sequence could interact with the distal side or some other portion of the same Hfq molecule. In fact, it was demonstrated recently that a U-rich RNA oligonucleotide corresponding to the internal Hfq-binding site of DsrA interacts with not only the proximal site but also the distal site and the rim of the Hfq hexamer (Wang et al 2011). An alternative possibility would be that the poly(U) tail of one SgrS molecule is recognized by the proximal side of one Hfq hexamer, while the internal stem-loop/U-rich sequence binds the distal side of another Hfq hexamer as proposed recently for DsrA-Hfq interaction (Wang et al 2011).…”
Section: (B) Properties Of Sgrs-s Variants It1568 Cells Harboring Inmentioning
confidence: 99%
See 1 more Smart Citation
“…If this were the case, it would be possible that the proximal side of Hfq binds the terminator poly(U) tail, while the internal stem-loop/U-rich sequence could interact with the distal side or some other portion of the same Hfq molecule. In fact, it was demonstrated recently that a U-rich RNA oligonucleotide corresponding to the internal Hfq-binding site of DsrA interacts with not only the proximal site but also the distal site and the rim of the Hfq hexamer (Wang et al 2011). An alternative possibility would be that the poly(U) tail of one SgrS molecule is recognized by the proximal side of one Hfq hexamer, while the internal stem-loop/U-rich sequence binds the distal side of another Hfq hexamer as proposed recently for DsrA-Hfq interaction (Wang et al 2011).…”
Section: (B) Properties Of Sgrs-s Variants It1568 Cells Harboring Inmentioning
confidence: 99%
“…In fact, it was demonstrated recently that a U-rich RNA oligonucleotide corresponding to the internal Hfq-binding site of DsrA interacts with not only the proximal site but also the distal site and the rim of the Hfq hexamer (Wang et al 2011). An alternative possibility would be that the poly(U) tail of one SgrS molecule is recognized by the proximal side of one Hfq hexamer, while the internal stem-loop/U-rich sequence binds the distal side of another Hfq hexamer as proposed recently for DsrA-Hfq interaction (Wang et al 2011). Structural studies on the Hfq-functional sRNA complexes are certainly required to clarify why the hairpin structure is needed for the efficient Hfq binding and how exactly Hfq binds to the Hfq-binding modules to facilitate base-pairing between sRNAs and target mRNAs.…”
Section: (B) Properties Of Sgrs-s Variants It1568 Cells Harboring Inmentioning
confidence: 99%
“…The Hfq core has two distinct faces; these proximal and distal faces have both been shown to be involved in RNA binding. In particular, U-rich RNA sequences, often found in sRNAs, have been shown to interact with the proximal face of Hfq, while A-rich sequences, or A-R-N repeats (where R is a purine nucleotide and N is any nucleotide), usually found in mRNAs but also present in some sRNAs, have been shown to interact with the distal face (Schumacher et al 2002;Mikulecky et al 2004;Updegrove et al 2008;Link et al 2009;Sauer and Weichenrieder 2011;Wang et al 2011). Recently, sRNA binding to the lateral surface of the Hfq core has also been identified (Updegrove and War-tell 2011;Sauer et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We were unable to identify any reasonable candidates in our crystallization condition that were likely to reside in this position and believe that this is simply an accumulation of spurious electron density along a pseudocrystallographic axis. It is worth noting, however, that in the higher resolution crystal structure of Ec Hfq bound to proximal face-bound AU 6 A (Wang et al 2011), a water coordinated metal ion was observed in a similar location and made contacts to the RNA phosphate backbone. Although this might still be the case for the Lm Hfq-U 6 complex, placement of a similarly hydrated metal ion is too speculative at the current resolution.…”
Section: Lm Hfq Recognition Of Uridinementioning
confidence: 93%
“…2). Further, in common among Hfq proteins is the hydrogen bond made between a conserved glutamine (Lm Hfq residue Q9; Ec [Wang et al 2011[Wang et al , 2013, St [Sauer and Weichenrieder 2011], and Sa [Schumacher et al 2002] Hfq residue Q8) and the exocyclic O2 atom of uracil. In all four proteins, the Oε of this glutamine typically hydrogen bonds to the side chain ε amino group of a conserved lysine residue (K58 in Lm Hfq, K57 in Sa Hfq, and K56 in Ec and St Hfq).…”
Section: Lm Hfq Recognition Of Uridinementioning
confidence: 99%